Examining the impact of visitors emotion and perceived quality towards satisfaction and revisit intention to theme parks. - Norzalita Abd Aziz,; Ahmad Azmi M.Ariffin,; Nor Asiah Omar,; Chin Evin, (Penerbit Universiti Kebangsaan Malaysia, 2012)
Theme parks attempt to create enjoyable and amazing experiences for visitors. As a result,theme parks are important sectors within the tourism industry, which has grown dramatically with theme parks becoming the main tourist destinations in some countries. The purpose of this research is to analyzehow the perceived quality and emotions of visitors in Malaysias theme park environments influence their satisfaction and behavior intentions to revisit.Three main factors that will influence visitors satisfaction towards theme parks and their behavioral intentions to revisit are perceived quality, arousal-based experiences and pleasure-based experiences.This study involves 320 respondents, significant predictors that influence the satisfaction among the theme park visitors are arousal-based experiences and perceived services quality. The parks management can use the findings of this study in planning and executing marketing strategies to improve the theme park service offerings.